Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, -(-15+125-81)-(-85+75-19+100)
=-15-125+81-(-85)-75+19-100
=-140+81-(-85)-75+19-100
=-59-(-85)-75+19-100
=-16-75+19-100
=-91+19-100
=-72-100
=-172
\(\frac{5}{6}+\frac{11}{12}+\frac{19}{20}+...+\frac{89}{90}\)
\(=1-\frac{1}{6}+1-\frac{1}{12}+1-\frac{1}{20}+...+1-\frac{1}{90}\)
\(=8-\left(\frac{1}{6}+\frac{1}{12}+\frac{1}{20}+...+\frac{1}{90}\right)\)
\(=8-\left(\frac{1}{2.3}+\frac{1}{3.4}+\frac{1}{4.5}+...+\frac{1}{9.10}\right)\)
\(=8-\left(\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+....+\frac{1}{9}-\frac{1}{10}\right)\)
\(=8-\left(\frac{1}{2}-\frac{1}{10}\right)\)
\(=\frac{38}{5}\)
Bài 1:
a, 58.32 + 58.68 - 800
= 58.(32 + 68) - 800
= 58.100 - 800
= 5800 - 800
= 5000
b, 12020 + 280 : [55 - (7 - 4)3]
= 12020 + 280 : [ 55 - 33 ]
= 12020 + 280 : [ 28]
= 12020 + 10
= 12030
c, (96 - 19 - 45) - (55 + 96 - 119)
= 96 - 19 - 45 - 55 - 96 + 119
= (96 - 96) + (119 - 19) - (45 + 55)
= 0 + 100 - 100
= 0
a) \(\left(55-27\right)+\left(27+30-55\right)\)
\(=55-27+27+30-55\)
\(=\left(55-55\right)+\left(-27+27\right)+30\)
\(=30\)
b) \(\left(75+35+15\right)-\left(15-75+35\right)\)
\(=75+35+15-15+75-35\)
\(=\left(75+75\right)+\left(35-35\right)+\left(15-15\right)\)
\(=75+75\)
\(=150\)
a) \(\frac{5}{6}+\frac{11}{12}+\frac{19}{20}+\frac{29}{30}+\frac{41}{42}+\frac{55}{56}+\frac{71}{72}+\frac{89}{90}\)
\(=1-\frac{1}{6}+1-\frac{1}{12}+1-\frac{1}{20}+1-\frac{1}{30}+1-\frac{1}{42}+1-\frac{1}{56}+1-\frac{1}{72}+1-\frac{1}{90}\)
\(=8-\left(\frac{1}{6}+\frac{1}{12}+\frac{1}{20}+\frac{1}{30}+\frac{1}{42}+\frac{1}{56}+\frac{1}{72}+\frac{1}{90}\right)\)
\(=8-\left(\frac{1}{2.3}+\frac{1}{3.4}+\frac{1}{4.5}+\frac{1}{5.6}+\frac{1}{6.7}+\frac{1}{7.8}+\frac{1}{8.9}+\frac{1}{9.10}\right)\)
\(=8-\left(\frac{3-2}{2.3}+\frac{4-3}{3.4}+\frac{5-4}{4.5}+\frac{6-5}{5.6}+\frac{7-6}{6.7}+\frac{8-7}{7.8}+\frac{9-8}{8.9}+\frac{10-9}{9.10}\right)\)
\(=8-\left(\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+\frac{1}{4}-\frac{1}{5}+\frac{1}{5}-\frac{1}{6}+\frac{1}{6}-\frac{1}{7}+\frac{1}{7}-\frac{1}{8}+\frac{1}{8}-\frac{1}{9}+\frac{1}{9}-\frac{1}{10}\right)\)
\(=8-\left(\frac{1}{2}-\frac{1}{10}\right)=7,6\)
b) Bạn làm tương tự.
A = (1 -1/2) + (1 - 1/6) + (1 - 1/12) + (1 - 1/20 ) + ...+ (1 - 1/ 90)
= (1+1+1+1+1+1+1+1+1) - ( 1/2 - 1/6 - 1/12 - 1/ 20 - ...- 1/90)\(=9-\left(\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+\frac{1}{4.5}+...+\frac{1}{9.10}\right)=9-\left(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{9}-\frac{1}{10}\right)\)\(=9-\left(1-\frac{1}{10}\right)=\frac{81}{10}\)
\(9-A=1-\frac{1}{2}+1-\frac{5}{6}+1-\frac{11}{12}+1-\frac{19}{20}+...+1-\frac{89}{90}\)
\(\Leftrightarrow9-A=\frac{1}{1\cdot2}+\frac{1}{2\cdot3}+\frac{1}{3\cdot4}+...+\frac{1}{9\cdot10}\)
\(\Leftrightarrow9-A=\frac{2-1}{1\cdot2}+\frac{3-2}{2\cdot3}+\frac{4-3}{3\cdot4}+...+\frac{10-9}{9\cdot10}\)
\(\Leftrightarrow9-A=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{4}+...+\frac{1}{9}-\frac{1}{10}=1-\frac{1}{10}=\frac{9}{10}\)
\(\Leftrightarrow A=9-\frac{9}{10}=\frac{81}{10}\)
a) -48 + (-35 + 19) - (32 + 45 + 21)
= -48 - 35 + 19 - 32 - 45 - 21
= (-48 - 32) - (35 + 45) + (19 - 21)
= -80 - 80 - 2
= -162
b) -47 + (38 - 13) - (-52 + 31 - 91)
= -47 + 38 - 13 + 52 - 31 + 91
= (-47 - 13) + (38 + 52) - 31
= -60 + 90 - 31
= 30 - 31 = -1
c) 54 + (-37) - (+70) + (-163) - (-246) + (-230
= 54 - 37 - 70 - 163 + 246 - 230
= (54 + 246) - (37 + 163) - (70 + 230)
= 300 - 200 - 300
= -200
còn lại tự lm